Effect of Papaya flower ethanolic extract (Carica Papaya) on the time kill of tetracyclin against Escherichia Coli - Anugraheni Anugraheni; Chylen Setiyo Rini (Pharmaciana, 2023)
Papaya (Carica papaya) is found throughout Indonesia. Papaya flowers contain saponin, tannin, alkaloid, and flavonoid compounds which functions as antibacterial. Escherichia coli is a Gram-negative rod bacteria that could be found in the human large intestine as a cause of diarrhea. The study aimed to determine the effect of papaya flower extract and a combination of papaya flower extract with tetracycline antibiotics using the smallest concentration capable of inhibiting 50% of bacterial growth against Escherichia coli bacteria ATCC 25922 using the time-kill test method. This study was the method of Minimum Inhibitory Concentration (MIC) and time-kill. The MIC of the ethanol extract of papaya flower was 2 mg/mL. The time-kill test showed that the death phase was occurred at 4 - 24 hours. The bacteriostatic effect of the extract was obtained at 0 hours to 24 hours, while the antibiotic and its combination with the extracts had a bactericidal effect at 8 hours and 24 hours.